2022
DOI: 10.3390/healthcare10020243
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Reputation of Assistive Technology Resources Center: An Example from Yunlin County, Taiwan

Abstract: By the end of 2020, a total of 34 multifunctional Assistive Technology Resources Centers (ATR centers) were set up in 22 counties and cities in Taiwan. This study examines the perceptions of the users and their caregivers of the government-established ATR centers in Taiwan and examines the impact on the reputation of the public institution. The research framework and hypotheses were developed by examining the factors of “service convenience”, “center-related factors”, “justice”, and “perceived value” and using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In a study on the impact of ATR center services on the reputation of public agencies by T.-Y. Chang and Huang [16], it was pointed out that assistive device users value service convenience, service convenience has a positive impact on the reputation of public agencies, and both have a positive impact on the perceived value of services.…”
Section: Service Conveniencementioning
confidence: 99%
See 4 more Smart Citations
“…In a study on the impact of ATR center services on the reputation of public agencies by T.-Y. Chang and Huang [16], it was pointed out that assistive device users value service convenience, service convenience has a positive impact on the reputation of public agencies, and both have a positive impact on the perceived value of services.…”
Section: Service Conveniencementioning
confidence: 99%
“…In a study on the influence of reputation in assistive technology service centers, it was found that service convenience has a direct influence on reputation. On the other hand, ATR center-related factors such as brand, service environment, or service system design have an indirect impact on reputation [16]. Image and reputation, both representing positive quality in a company's external public relations, belong to the structures of asymmetric and symmetric models, respectively [35,36].…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%
See 3 more Smart Citations